IDENTIFIKASI PENYAKIT NENAS (ANANAS COMOSUS L.) DAN TINGKAT SERANGANNYA DI DESA RIMBO PANJANG KECAMATAN TAMBANG KABUPATEN KAMPAR PROVINSI RIAU - Fifi Puspita; Yetti Elfina; Siti Aminah (Universitas Riau, 2004)
Pineapple (Ananai cnmo.ms L.) is a fmit, whicli has high economic value because of its wide variety of uses. Itis not only consumed fresh, but also made into syrup, taffy, andother candies, Jam and dried into chips. Thecultivation pineapple in the Rinibo Panjang Village, Tambang District, Subprovince of Kampar, Province ofRiau still uses traditional growing and culUvication methods, which result in low productivity. Conservationand diseases control are areas that need to be iraprovcd.Thc purpose of this research Ls to identifify the diseasesbased on characteristic morphology and that attack stage at the pineapple. The research was conducted in Pestand Plant diseases Laboratory of Agricultural Faculty at Riau University.This research used survey methodbased on field area, quantity of population, and plants were produced. The results of the research indicated thatsire two type of diseases attacking the pineapple crops. The First is a leaf spot caused Curvulariamaculans,infecting some 34.6 % in the field 4, The second is decay the fruits caused Thiehviopsis paradoxa, and wasfound in 32 % of the crop in field 2.